The improvement of biomechanical variables at Albanian Elite boxers - Bendo, Aida; Bushati, Sead; Bushati, Marsida (Edelweiss Applied Science and Technology, 2024)
Boxing is a sport of self-defense art that utilizes compounds of muscle power, brain and conscience realistically and rationally. The speed required in boxer sports is very dominant in the speed of stimulating reaction of arms and legs when defending and responsive in attacking with a blow or kick. Reaction time is defined as the time elapsed between the stimulus and the response time to the stimulus, which is the determining factor in terms of performance level superiority in many sports branches and it is possible to improve it with training. The purpose of this study is to evaluate the effect of fit light training at elite Albanian boxers. The group in this study is consisted by 16 elite Albanian boxers, divided by an experimental group and a control group. At the experimental group, fit light training was used to collect data before and after training, while the basic boxing training was given to the control group. The paired samples t-test and the independent t-test were used to evaluate the data. The statistical significance at p<0.05 was set. The results have revealed that variables of, and in pretest data in control group were in similar levels, in the posttest data they were respectively: TR arm and leg higher and PF lower, for the experimental group. It can be concluded that the fit light training method is very effective and it is highly recommended to use widely for the training of all boxers, not only the elite ones.